SPLENIC FLEXURE MOBILIZATION DURING ANTERIOR RESECTION OF THE RECTUM FOR CANCER: SAFETY AND CANCER VALIDITY - V. V. Polovinkin; P. S. Pryn; V. V. Sapsay (Кубанский научный медицинский вестник, 2016)
The regularity of the splenic flexure mobilization during operations for rectal cancer is called in question. To assess if the splenic flexure mobilization during rectum resection has an impact on early postoperative complications rate, mortality and the number of lymph nodes examined. Prospective comparative study. 940 patients underwent a selective surgery for colorectal adenocarcinoma T1-4N0-2M0-1 during 2003-2014. Patients were divided into two groups: with the splenic flexure mobilization (n = 359), and without splenic flexure mobilization (n = 581). The early postoperative complications rate did not have statistically significant difference. Postoperative mortality had statistically insignificant difference (1,1% vs. 2,9%, p = 0.06). The number of examined lymph nodes increases if the splenic flexure mobilization is performed (13±7,3 vs. 10,6 ± 6,6, p